(untitled) (Journal of the College of Basic Education, 2023)
The emphasis on developing the educational process and providing it with everything that is new and developedof the methods, methods and strategies in the teaching process, and in a manner appropriate to the technical developmentContemporary scientific progress, which is one of the important features of our time.The person of the researcher through the process of communication in the field of field teaching and his use of methodsVarious teaching methods in educational institutes and colleges, and his observations and field visits.Primary and secondary schools have a weak attitude among students in academic subjects, especiallyGeography as a practical subject that requires thinking and analysis, which prompted the researcher to feelAwareness of this problem and an attempt to adopt one of the modern methods and teaching methods thatIt would raise the academic and achievement level, for this reason the researcher chose cooperative learning (teamlearning) because of its positive aspects and its impact on the attitudes of female studentsPreparatory four towards natural geography, so the research problem is manifested by emphasizingStudies and research on the low level of attitude and achievement of students in the subject of geography, which attributedThe reason for this is the teaching methods and methods that emphasize the positive role of the teacher in the process.teaching, as it is the main source of information and its goal is to memorize information for learners, whichleads to the development of their mental abilities